Pelaksanaan Salat Jumat di Tempat Kerja Selain Masjid di Masa Pandemi Covid-19 Berdasarkan Perspektif Hukum Islam - Mahmuddin, Ronny; Akbar, Fadhlan (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed to describe the law of Friday prayers in offices or workplaces such as in fields, halls, mushalla, and for example in other places than mosques during the Covid-19 pandemic based on the propositions of the Koran, hadith, and fiqh principles as well as the opinions of the scholars. This type of research was a qualitative descriptive study using a literature review method in collecting data with a legal-normative approach. The results of this study indicate that the law of conducting Friday prayers in other than mosques during the Covid-19 pandemic is permissible based on the propositions of the Koran, hadith, fiqh principles, and the words of the scholars. However, if the nearest mosque can accommodate all worshipers even though they are in a tenuous prayer position during the Covid-19 pandemic, then employees are required to conduct Friday prayers at the mosque based on the opinion of most scholars, unless there is a necessity such as a remote mosque or a small mosque which cannot accommodate many worshipers or other justified age, Friday prayers are allowed at their workplace. The implementation of this research is expected to contribute theoretically and practically to religious leaders, parties with special interests, and society in general.